Hop-Derived Iso-α-Acids in Beer Improve Visual Discrimination and Reversal Learning in Mice as Assessed by a Touch Panel Operant System - Ayabe, Tatsuhiro; Ohya, Rena; Ano, Yasuhisa (Frontiers in Behavioral Neuroscience, 2019)
Dementia and cognitive decline have become worldwide health problems due to rapid growth of the aged population in many countries. We previously demonstrated that single or short-term administration of iso-α-acids, hop-derived bitter acids in beer, improves the spatial memory of scopolamine-induced amnesia model mice in the Y-maze and enhances novel object recognition in normal mice via activation of the vagus nerve and hippocampal dopaminergic system. However, these behavioral tests do not replicate the stimulus conditions or response requirements of human memory tests, and so may have poor translational validity. In this report, we investigated the effects of iso-α-acids on visual discrimination (VD) and reversal discrimination (RD) using a touch panel-based operant system similar to that used for human working memory tests. In the VD task, scopolamine treatment reduced correct response rate and prolonged response latency in mice, deficits reversed by prior oral administration of iso-α-acids. In the RD task, administration of iso-α-acids significantly increased correct response rate compared to vehicle administration. Previous studies have reported that dopamine signaling is involved in both VD and RD learning, suggesting that enhancement of dopamine release contributes to improved memory performance in mice treated with iso-α-acids. Taken together, iso-α-acids improve VD and RD learning, which are considered high-order cognitive functions. Given the translational advantages of the touch panel-based operant system, the present study suggests that iso-α-acids could be effective for improvement of working memory in human dementia patients.